Photoelectric properties of metal-porous silicon-silicon planar heterostructures - Brodovoi, A.V.; Brodovoi, V.A.; Skryshevskyi, V.A.; Bunchuk, S.G.; Khnorozok, L.M. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2002)
Dark and light I-V characteristics as well as spectral curves of planar Ni-porous silicon-p-Si-Ni heterostructures have been studied. It is shown that photogeneration in heterostructure occurs both in the region of thin porous silicon layer and p-Si base. Avalanche breakdown is observed in the heterostructure at applied voltage biases V > 8-10 V and T = 77 K. The coefficient of multiplying at V = 11 V achieves 60 (dark) and 200 (light), which is close to that of silicon n+-p-i-p+ avalanche photodiodes.